1979-1980 シーズン ニ オケル ナンキョクカイ ウミドリ ノ モクシ カンサツ - 大山, 佳邦; オオヤマ, ヨシクニ; 内藤, 靖彦; ナイトウ, ヤスヒコ; 中村, 一恵; ナカムラ, カズエ; Ohyama, Yoshikuni; Naito, Yasuhiko; Nakamura, Kazue (1981)
P(論文) 1979～1980年の夏期, 南極海でオキアミの漁業調査を行った2隻の船および国際捕鯨委員会によるミンククジラの個体数調査船に海鳥の調査を依頼した。調査海域は主として63°S以南, パックアイス帯までの間で, 東西には0°E～115°Eに及ぶ広い海域にわたった。調査は1日1回, 10分間(時刻は不定)に出現する海鳥の種類と個体数を, 南極研究科学委員会鳥類小委員会の勧告したデータシートを若干改変したものに記入することであった。今回の調査で東西に広い範囲にわたって出現した鳥は主としてこの時期に南極大陸あるいはその付近の島々で繁殖している種類であった。ナンキョクフルマカモメ, ユキドリ, マダラフルマカモメ, アシナガコシジロウミツバメなどがそれである。また亜南極の島々で繁殖しているハイイロアホウドリ, ハイイロミズナギドリもよく現れた。これらは外洋性の習性が強く, 夏にはパックアイス近辺まで南下する種類である。 Visual observations of sea birds in the Southern Ocean were carried out on board three ships during the austral summer of 1979-1980; two ships for exploratory fishing of krill, a factory ship SHINANO MARU and a trawler ORIENTO MARU, and one ship for the population census of minke whale, KYO MARU (a catcher). The surveyed area was south of 63°S between 0°E and 115°E in longitude. Ten minutes within a day were allocated for bird observations. The species and the number of sea birds observed in ten minutes were recorded on a data sheet which was a slightly modified standard recording card of SCAR prepared for this survey. The bird species that occurred in a wide longitudinal range were the breeders on the Antarctic Continent or on the adjacent island in austral summer, i. e. antarctic petrel, snow petrel, cape pigeon, and Wilson's storm petrel. Light-mantled sooty albatross and sooty shearwater that are breeding on the sub-Antarctic islands also occurred in a wide range; these two birds are highly pelagic in habit and often disperse south to the edge of the pack ice in summer. departmental bulletin paper